Professional ADO.NET 3.5 with LINQ and the Entity Framework - Jennings, Roger (Wrox professional guides., 2009)
Language Integrated Query (LINQ), as well as the C# 3.0 and VB 9.0 language extensions to support it, is the most import single new feature of Visual Studio 2008 and the .NET Framework 3.x. LINQ is Microsoft's first attempt to define a universal query language for a diverse set of in-memory collections of generic objects, entities persisted in relational database tables, and element and attributes of XML documents or fragments, as well as a wide variety of other data types, such as RSS and Atom syndication feeds. Microsoft invested millions of dollars in Anders Hejlsberg and his C# design and.